DESKRIPSI PEMAHAMAN KONSEP SISWA DALAM MATERI OPERASI HITUNG BILANGAN PECAHAN DI SMP BOEDI OETOMO - Fatmawati, Syarifah; Jamiah, Yulis; Hamdani, Hamdani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to describe the understanding of students' concepts in the matter of addition and subtraction operations of fractions which are not the same denominator. An indicator of understanding concepts : 1) students' understanding of expressing fractions into other forms of fraction that are worth the sum; 2) students' understanding of using, utilizing, selecting procedures for addition and subtraction of fractions. This research uses descriptive method in the form of case study research with research subjects in this study were seventh grade students of Boedi Oetomo Junior High School. The results showed that in the of understanding concept that states fractions to other forms of fractions that are worth the sum in the addition operation and subtraction operation problems with different denominator are included in the good category but understanding the concept of using, utilizing, selecting the procedure for addition and subtraction operations for fractions with different denominator are included in the low category. Keywords : Understanding of concepts, Counting operation, fractions material